O design dos cursos e a produção de sentidos sobre a qualidade das interações na EAD - Silva, Jones Quadros da (Universidade do Vale do Rio dos Sinos, 2012)
Since the emergence of the Distance Education (DE) in Brazil, the regulatory frameworks of this type of education have changed considerably. The search for the quality in higher education, the achievement of the market demands and of the requirements of the Ministry of Education are factors that are not always articulated in an equitable manner. Depending on the region, the level of competitiveness among private institutions of higher education and the local culture, these factors may conflict, directly influencing the design of university courses and, therefore, the quality of the training. In addition to these factors that relate to the institutional aspects, among the various elements that make up the daily life of the DE courses, the quality of the interactions can be considered as decisive for the development of academic activities. What are the meanings attributed by managers, teachers, tutors and students to the quality of the interactions that occur in the context of higher education courses in DE? How do these senses articulate with the design of these courses - their operating regimes, monitoring and learning evaluation? Moreover, with regard to the digital culture, the profile of the people who enter the DE is quite different, as well as the motivations that guide the choice for this type of education, these motivations are not always in tune with the technical and symbolic interactions that belong to digital media. How do the meanings attributed to DE by professionals and students justify the quality of the distance interactions in the context of higher education courses? Based on the concept of cognitive ecology, the objective of this project is to investigate and to study the production of meanings about the quality of the interactions in DE. In order to do so, we intend to examine the tensions between the regulatory frameworks of the Brazilian DE, the design of university courses and the meanings that managers, teachers, tutors and students attribute to the DE, so as to examine the possible effects of these tensions in the production of meanings about the quality of the interactions. By establishing a relationship between legal or institutional factors and the production of meanings that arise in the context of digital interactions, this study intends to provide subsidies to both public policies sphere of Higher Education - in constant dialogue with the reformulation of the regulatory frameworks – and for the training and informative sphere – regarding a greater harmony between the symbolic and technical requirements of a promising digital culture and the profile of the participants of DE.
Keywords: Educação a distância; Interações; Design dos cursos; Produção de sentidos; Distance education; Interactions; Courses` design; Production of meanings; ACCNPQ::Ciências Humanas::Educação